Relationship between urinary bisphenol A and age at menarche among adolescent girls: A study in Sumatera Utara Province, Indonesia - Putri, Vriancha A.; Arto , Karina S.; Lubis , Aridamuriany D.; Dangana, Amos; Chiu, Yao-Hsuan (Narra Sains Indonesia, 2024)
Bisphenol A (BPA) is an endocrine-disrupting chemical widely used in various consumer products. Due to its estrogenic properties, BPA exposure is suspected to influence reproductive development, particularly the timing of menarche in adolescent girls. The aim of this study was to assess the relationship between urinary BPA levels and the age at menarche among adolescent girls in Sumatera Utara Province, Indonesia. A cross-sectional study was conducted in January 2023 involving 30 adolescent girls aged 9–14 years attending junior high school in Sumatera Utara. Data on age, body weight, height, and body mass index (BMI) were collected. Urinary BPA levels were detected using high-performance liquid chromatography (HPLC). The Mann-Whitney U test was employed to determine the association between BPA detection and age at menarche. BPA was detected in the urine of 3 out of 30 participants. The median age at menarche for girls with detectable BPA was 11 years, while those without detectable BPA had a median age of 11 (ranging from 10 to 12 years). The difference in age at menarche between the two groups was not statistically significant (p=0.646). In conclusion, this study did not find a significant association between urinary BPA levels and the timing of menarche among adolescent girls in Sumatera Utara Province. Further research with a larger sample size and consideration of additional confounding factors is recommended to better understand the potential impact of BPA on pubertal development.